Effectiveness Test of The Combined Extract of Papaya Seeds (Carica Papaya L.) and Sweet Orange Peel (Citrus Sinesis L.) as A Larvicide Against Aedes Aegypti Mosquitoes: Penelitian - Helfi Nolia; Karo, Marina br. (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Dengue Hemorrhagic Fever (DHF) remains one of the most significant public health problems in Indonesia. This study aims to determine the effectiveness of a mixture of papaya seed (Carica papaya L.) and sweet orange peel (Citrus sinensis L.) extracts as a botanical larvicide against Aedes aegypti mosquito larvae. A quasi-experimental study was conducted using a Completely Randomized Design with five treatments and four replications. Three concentrations (1%, 1.5%, and 2%) of the mixed extract were tested with observation for 12 hours. The mortality rate of larvae increased with the concentration: 1% (30%), 1.5% (67.5%), and 2% (100%). ANOVA and Duncan tests confirmed significant differences (p<0.05). The synergistic action of flavonoids, saponins, tannins, papain, and limonoids enhanced larval mortality, indicating the potential of plant-based larvicides as an eco-friendly alternative to synthetic chemicals.